Relationship between microcephaly and Zika virus during pregnancy: a review - Santos,Gerusinete Rodrigues Bastos dos (2018)
SUMMARY AIM: the present study analysed the association between Zika-virus and microcephaly during the gestational period of women in Brazil. Methodology: Systematic reviews of intervention research, current publications of clinical investigations were used systematic search strategies in three electronic databases PubMed, SciELO and Google academic. The following keywords were used: Microcephaly, gestation, Zika-virus to perform the search, and 1020 articles were obtained after exclusion, 45 were left and 35 were eligible. The collection period was from 2004 to 2017. Results: Epidemiological data suggest a temporal association between the quantitative increase and the Zika-virus epidemic, especially in Northeast Brazil. It is not consensual to measure the cephalic perimeter curve to be considered. Conclusion: Given this, the application of techniques to accurately diagnose the relationship between causes and effects in the pathogenesis of Zika virus infection in the central nervous system should be prioritized.